CDH1, DLEC1 and SFRP5 methylation panel as a prognostic marker for advanced epithelial ovarian cancer. (16th October 2018) - Lin, Han-Wei; Fu, Chi-Feng; Chang, Ming-Cheng; Lu, Tzu-Pin; Lin, Hsiu-Ping; Chiang, Ying-Cheng; Chen, Chi-An; Cheng, Wen-Fang
Aim: To investigate the CDH1, DLEC1 and SFRP5 gene methylation panel for advanced epithelial ovarian carcinoma (EOC).Materials & methods: One hundred and seventy-seven advanced EOC specimens were evaluated by methylation-specific PCR. We also used The Cancer Genome Atlas dataset to evaluate the panel.Results: The presence of two or more methylated genes was significant in recurrence (hazard ratio [HR]: 1.91 [1.33–2.76]; p = 0.002) and death (HR: 1.96 [1.26–3.06]; p = 0.006) in our cohort. In The Cancer Genome Atlas dataset, the presence of two or three methylated genes was significant in death (HR: 1.59 [1.15–2.18]; p = 0.0047) and close to the significance level in recurrence (HR: 1.37 [0.99–1.88]; p = 0.058).Conclusion: The CDH1, DLEC1 and SFRP5 methylation panel is a potential prognostic biomarker for advanced EOC. Graphical abstract: